2017
DOI: 10.1186/s13756-017-0195-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the susceptibility of Acinetobacter baumannii isolates to antiseptics and disinfectants: comparison between clinical and environmental isolates

Abstract: BackgroundThis study aims to assess the susceptibility of Acinetobacter baumannii isolates to the antiseptics and disinfectants commonly used, and to the non-approved product.MethodsThis is a prospective study carried out from February to August 2015, in the Bacteriology department of Mohammed V Military Teaching hospital of Rabat on A.baumannii isolates collected from colonized and/or infected patients and environmental samples. The antiseptics and disinfectants susceptibility testing was assessed using the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
4
12
1
Order By: Relevance
“…baumannii were well in agreement with two in vitro studies [21,22]. On the contrary, the results with regard to MRSA were not in concurrence with an earlier study [23] who has shown a better efficacy for chlorhexidine against MRSA.…”
Section: Discussionsupporting
confidence: 82%
“…baumannii were well in agreement with two in vitro studies [21,22]. On the contrary, the results with regard to MRSA were not in concurrence with an earlier study [23] who has shown a better efficacy for chlorhexidine against MRSA.…”
Section: Discussionsupporting
confidence: 82%
“…Another report also showed the spread of carbapenem-resistant A. baumannii belonging to CC92 (Chen et al, 2017 ); however, biocide susceptibility phenotypes were not assessed. Together with the antibiotic and biocide susceptibility phenotypes of these clones we studied, the present study continues to argue the importance to monitor the biocide susceptibility to A. baumannii and to promote biocide stewardship in hospitals (Kampf, 2016 ; Lanjri et al, 2017 ).…”
Section: Discussionmentioning
confidence: 58%
“…In addition, these species represent both gram-positive and -negative bacteria. Although our study did not include other common bacterial pathogens causing pneumonia such as Staphylococcus aureus , Pseudomonas aeruginosa , Haemophilus influenzae and Acinetobacter baumannii , the efficacy of PVP-I against these pathogens has already been demonstrated in previous studies [ 16 , 18 , 32 , 33 , 41 , 46 ].…”
Section: Discussionmentioning
confidence: 99%